(3GdJhGQIs
(3ChdgG (B:s
(3GdCMO GdChd ef GdUhe GdebOS bGd Ef GdSjO GdeSjM Yde Cf ajdHS eTJGb Edi GddMhb Hg aYfOeG bGd dg CHJYfi dMbg HZjQ Gddhe hdG JCNQ hdh de jYde GdSjO Cfg Ph UdGM s
(3BNQgG (B:s
(3aEf cd EfSGf fGbU hGddg gh GdcGed cJHJg HjOi hGdNW jTgO di Cfi SCJQcg jhekG hCQJMdi jG SGcf GdOGQ dGJfSG GdQMjd CZOkG acd SGcf OGQ Sha jQJMdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdOjGfGJ GdCNQis